Atención al cliente en la Gasolinera Clyan, en la Parroquia Isla de Bejucal-Cantón Baba durante el periodo 2023. - Arriciaga Salcedo, Melany Mariuxi (2025)
The study conducted at gas station Clyan, located in the parish Isla the Bejucal, Canton Baba during 2023, reveals significant shortcomings in customer service that adversely affect customer perception and loyalty. This descriptive and cross-sectional research combined quantitative surveys with qualitative interviews to identify critical factors impacting the customer experience. Results indicate that a high percentage of respondents expressed dissatisfaction with essential aspects such as long waiting times, unfriendly service from staff, and poor communication of information, all of which lead to frustration and a low likelihood of recommending the service. In addition, the quality of service was generally rated as poor, with deficiencies noted in the station's infrastructure and cleanliness, further reinforcing a negative overall impression of the establishment. The analysis highlights that the primary causes of low satisfaction stem from inadequate ongoing staff training and the absence of effective strategies to reduce waiting times. The manager’s interview confirmed the urgent need for corrective measures, including the implementation of digital queuing systems, process automation, and targeted training programs aimed at enhancing communication skills and problem resolution. Proposed improvements also emphasize the optimization of physical infrastructure and the establishment of continuous feedback mechanisms to better align service offerings with customer expectations. By addressing these critical issues, gas station Clyan can work towards delivering a more positive customer experience, which is essential for increasing customer retention and strengthening its competitive position in the local market.